2022
DOI: 10.3390/foods11182915
|View full text |Cite
|
Sign up to set email alerts
|

Surface Defect Detection of Fresh-Cut Cauliflowers Based on Convolutional Neural Network with Transfer Learning

Abstract: A fresh-cut cauliflower surface defect detection and classification model based on a convolutional neural network with transfer learning is proposed to address the low efficiency of the traditional manual detection of fresh-cut cauliflower surface defects. Four thousand, seven hundred and ninety images of fresh-cut cauliflower were collected in four categories including healthy, diseased, browning, and mildewed. In this study, the pre-trained MobileNet model was fine-tuned to improve training speed and accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“… Refs. Dataset Techniques Accuracy (%) 11 Sample images of cauliflower taken from Bangladesh Random forest 81.68 13 2500 images of cauliflower Inception V3 93.93 14 776 images of cauliflower Random Forest 89 16 Images of Xuebai MobileNetV1 95.63 17 Images of Eggplant diseases DenseNet201 99.06 Our Study VegNet EfficientNetB1 99.90 …”
Section: Analyzing the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Refs. Dataset Techniques Accuracy (%) 11 Sample images of cauliflower taken from Bangladesh Random forest 81.68 13 2500 images of cauliflower Inception V3 93.93 14 776 images of cauliflower Random Forest 89 16 Images of Xuebai MobileNetV1 95.63 17 Images of Eggplant diseases DenseNet201 99.06 Our Study VegNet EfficientNetB1 99.90 …”
Section: Analyzing the Resultsmentioning
confidence: 99%
“…Additionally, it demonstrated a highly impressive 99% accuracy in identifying cauliflower specimens afflicted by bacterial soft rot. In paper 16 , the researchers proposed a convolutional neural network (CNN) with transfer learning for the detection and classification of surface defects in fresh-cut cauliflower, aiming to overcome the inefficiencies of manual detection methods. The dataset comprises 4,790 cauliflower images categorized as diseased, healthy, mildewed, and browning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because previous studies have shown that these random features perform much better on standard transfer tasks than on random levels [ 44 ]. After the feature extraction, the extracted features (4096 dimensional) of Camellia oleifera fruit images are output through the penultimate fully connected layer of the VGG16-D FC model [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among these, InceptionV3 exhibited the highest accuracy at 90.08%, showcasing superior performance compared to the traditional machine learning approach. ( Li et al., 2022 ) introduced a detection and classification model for surface defects in fresh-cut cauliflower based on a CNN with transfer learning. A dataset comprising 4,790 images of fresh-cut cauliflower, categorized into healthy, diseased, browning, and mildewed classes, was collected for the study.…”
Section: Literature Reviewmentioning
confidence: 99%